Risks of fatal opioid overdose during the first year following nonfatal overdose. (1st September 2018) - Olfson, Mark; Wall, Melanie; Wang, Shuai; Crystal, Stephen; Blanco, Carlos
Highlights: Approximately 1% of nonfatal opioid overdoses have fatal overdoses within 1 year. Nonfatal opioid overdoses involving heroin are at increased risk of fatal overdose. Nonfatal overdoses requiring ventilation are at increased risk of fatal overdose. Abstract: Background: Little is known about risk factors for repeated opioid overdose and fatal opioid overdose in the first year following nonfatal opioid overdose. Methods: We identified a national retrospective longitudinal cohort of patients aged 18–64 years in the Medicaid program who received a clinical diagnosis of nonfatal opioid overdose. Repeated overdoses and fatal opioid overdoses were measured with the Medicaid record and the National Death Index. Rates of repeat overdose per 1000 person-years and fatal overdose per 100, 000 person-years were determined. Hazard ratios of repeated opioid overdose and fatal opioid overdose were estimated by Cox proportional hazards. Results: Nearly two-thirds (64.8%) of the patients with nonfatal overdoses (total n = 75, 556) had filled opioid prescriptions in the 180 days before initial overdose. During the 12 months after nonfatal overdose, the rate of repeat overdose was 295.0 per 1000 person-years and that of fatal opioid overdose was 1154 per 100, 000 person-years. After controlling for age, sex, race/ethnicity, and region, the hazard of fatal opioid overdose was increased for patients who had filled a benzodiazepine prescription in the 180 days prior to their initial overdose (HR = 1.71, 95%CI: 1.46–1.99), whose initial overdose involved heroin (HR = 1.57, 95%CI:1.30-1.89), or who required mechanical ventilation at the initial overdose (HR = 1.86, 95%CI = 1.50–2.31). Conclusions: Adults treated for opioid overdose frequently have repeated opioid overdoses in the following year. They are also at high risk of fatal opioid overdose throughout this period, which underscores the importance of efforts to engage and maintain patients in evidence-based opioid treatments following nonfatal overdose.